Nutritional interventions in muscle hypertrophy research: a scientometric analysis within the context of resistance training (1992–2025) - Chen, Wei (Journal of health, population and nutrition, 2025)
Background Muscle hypertrophy, as a central goal in sports training, rehabilitation interventions, and health promotion, relies on scientifically designed resistance training and appropriate nutritional strategies. However, research on the synergistic effects of nutritional interventions and resistance training in promoting muscle hypertrophy is characterized by thematic fragmentation, insufficient integration between mechanistic and applied research, and imbalances across different regions and population groups. Methods To systematically delineate the developmental trajectory and emerging trends in this field, a comprehensive search was conducted in the Web of Science Core Collection, initially retrieving 456 publications. After rigorous screening and data cleaning, 411 English-language articles published between 1992 and 2025 were retained for analysis. Scientometric techniques were applied to construct knowledge maps using three major tools: Bibliometrix (R 4.4.3), VOSviewer (1.6.20), and CiteSpace (6.2.6). Bibliometrix was used to analyze publication trends and thematic evolution; VOSviewer to map keyword co-occurrence and collaboration networks; and CiteSpace to detect citation bursts and visualize knowledge structures. Collectively, these methods facilitated the identification of high-frequency keywords, hotspot transitions, collaborative patterns, and underexplored thematic gaps. Results The results indicate that: (1) the combination of protein supplementation and resistance training represents the most prominent intervention strategy; (2) a stable tripartite research model has emerged, centering on the interaction among training, nutrition, and structural adaptation; (3) the thematic focus has gradually shifted from molecular mechanisms toward practical applications, emphasizing issues such as aging and functional improvement; and (4) notable research gaps remain, particularly the underrepresentation of women and Asian populations, insufficient attention to recovery, metabolism, and periodized nutrition, and the lack of a systematic framework for individualized interventions. Conclusion This study delineates the developmental trajectory, structural characteristics, and future directions of research in this field over the past three decades, providing empirical evidence and a theoretical foundation for the scientific formulation of muscle health enhancement strategies.